Comparative analysis of left ventricle function and deformation imaging in short and long axis plane in cardiac magnetic resonance imaging - Werner, Oscar; Martins, Duarte; Bertini, Federico; Bennati, Elena; Collia, Dario; Olivotto, Iacopo; Spaziani, Gaia; Baruteau, Alban-Elouen; Pedrizzetti, Gianni; Raimondi, Francesca (Frontiers in Cardiovascular Medicine, 2024)
Background: Advancements in cardiac imaging have revolutionized our understanding of ventricular contraction. While ejection fraction (EF) is still the gold standard parameter to assess left ventricle (LV) function, strain imaging (SI) has provided valuable insights into ventricular mechanics. The lack of an integrative method including SI parameters in a single, validated formula may limit its use. Our aim was to compare different methods for evaluating global circumferential strain (GCS) and their relationship with global longitudinal strain (GLS) and EF in CMR and how the different evaluations fit in the theoretical relationship between EF and global strain. Methods: Retrospective monocenter study. Inclusion of every patient who underwent a CMR during a 15 months period with various clinical indication (congenital heart defect, myocarditis, cardiomyopathy). A minimum of three LV long-axis planes and a stack of short-axis slices covering the LV using classical steady-state free precession cine sequences. A single assessment of GLS on long axis (LAX) slices and a double assessment of GCS and EF with both short axis (SAX) and LAX slices were made by a single experienced CMR investigator. Results: GCS-SAX and GCS-LAX were correlated (r=0.77,P<0.001) without being interchangeable with a high reproducibility for GCS, GLS and EF. EF calculated from LAX images showed an overestimation compared to EF derived from SAX images of 7%. The correlation between calculated EF and theoretical EF derived from SI was high (r= 0.88 with EF-SAX, 0.95 with EF-LAX). Data conclusion: This study highlights the need to integrate strain imaging techniques into clinical by incorporating strain parameters into EF calculations, because it gives a deeper understanding of cardiac mechanics.